Investigation of muscle fatigue during on-water rowing using surface EMG - Schwensow, D.; Hohmuth, R.; Malberg, H.; Schmidt, M. (44th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2022)
In this work, four different algorithms (fast Fourier transform FFT, short-time Fourier transform STFT, continuous wavelet transform CWT, and instantaneous frequency IF) for calculating median frequency (MDF) from surface EMG signals were investigated for studying muscle fatigue during a on-water rowing training. The study protocol included 5 consecutive parts with increasing stroke rate. Six athletes participated in the study aged 36.6+-14.6 years and a rowing experience of 6 to 35 years. We considered eight muscles: biceps brachii right, biceps brachii left, latissimus dorsi right, latissimus dorsi left, erector spinae right, erector spinae left, rectus femoris and biceps femoris. By applying Friedmann test, we found a significant difference in MDF behavior between algorithms in assessing muscle fatigue . Correlation analyses showed significant correlations between muscle activity duration tact and MDF, which differs for the four considered algorithms and should be taken into account in further experiments. With CWT showing the smallest correlation to tact it might be more robust against time window variations. Our study provides a basis for the development of improved methods for more robust, non-invasive, and continuous detection of muscle fatigue in experiments with dynamic on-water rowing study designs.